The Impact of Human Development Index on Marriage Rates - Abolfazl Shahabadi; , Fatemeh Sadat Hosseini (فصلنامه زن و جامعه)
Marriage, as a primary institution in society, is the first pillar of forming a family. Many critical variables of society such as fertility rate, population growth, resource utilization, consumption, saving, poverty, crime, etc. are affected by marriage. From this perspective, family studies needs considerable attention. Potential changes that occur during the development process in the societies can influence Individuals decision to marry, but the process of this effect is not clear. The Human Development Index, as a multidimensional index, can be a reliable index to understand the effect of the development process on the marriage rate. Therefore, this study aims to investigate the effect of the human development index on marriage rate in selected OECD and Non-OECD countries during the period 2000-2018 using the System Generalized Method of Moments (System_GMM). This study reveals that the human development index has a significant negative effect on the marriage rate in both of the study groups. However, the estimated coefficient in Non-OECD countries is lower than selected OECD countries. The coefficients of the life expectancy and income index are significantly negative in both of selected countries. The education index also has a significant negative effect on the marriage rate in Non-OECD countries, but its significance has not been confirmed in OECD countries. The results also show that the unemployment rate of men and the urban population growth in both groups of the countries have significantly negative effect on the marriage rate.